2011
DOI: 10.1682/jrrd.2010.05.0086
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle pacing with chronically implanted intramuscular Permaloc electrodes: A feasibility study

Abstract: Abstract-We tested the feasibility of stimulating upperintercostal and abdominal muscles plus the diaphragm by using chronically implanted intramuscular electrodes. During two survival surgeries with six dogs, intramuscular electrodes were implanted bilaterally in the three respiratory muscles. Standard stimulation of the diaphragm was conducted. The dorsolateral and ventrolateral abdominal wall areas were stimulated with a 25 mA current. The second to fourth intercostal spaces were stimulated to elicit the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
(73 reference statements)
1
16
1
Order By: Relevance
“…Respiratory responses in our prior studies were limited because of the use of too few electrodes, stimulating currents that were too low, and less than optimal electrode implant locations [19][20][21][22]. In the current study, improved methods to address each of these concerns were conducted and corresponding increases in respiratory responses were obtained.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Respiratory responses in our prior studies were limited because of the use of too few electrodes, stimulating currents that were too low, and less than optimal electrode implant locations [19][20][21][22]. In the current study, improved methods to address each of these concerns were conducted and corresponding increases in respiratory responses were obtained.…”
Section: Introductionmentioning
confidence: 93%
“…Esophageal pressure was monitored with a small balloon-tipped tube made from a surgical glove finger that was sealed at the end of the tube with glue and thread. The balloon and tube were filled with water and advanced orally to the esophagus to a location just rostral to the diaphragm [21][22]. The same type of balloontipped tube was used for abdominal pressure recording, and the balloon was introduced anally and advanced 23 cm into the colon to lie caudal to the diaphragm [21][22].…”
Section: Anesthesia Respiratory Instrumentation Apnea and Stimulatmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work is needed to study effects of stimulation on muscle fatigue and metabolic responses. In one long term study we identified a problem with securing Permaloc ® electrodes in extradiaphragmatic muscles [8]. To address this concern we plan to test opening the polypropylene securing barb and snaking the electrode lead away from the muscle exit site and using multiple sutures.…”
mentioning
confidence: 99%
“…For urinary applications, we are investigating Permaloc ® Intramuscular Electrodes for direct bladder wall stimulation and voiding as well as bilateral pudendal nerve stimulation for neuromodulation and bladder inhibition [3,[8][9][10][11]. Successful clinical methods of Magasi and Simon [12] for direct bladder wall stimulation and Possover et al [13] for pudendal nerve stimulation and neuromodulation are being followed.…”
mentioning
confidence: 99%